Creative Activities and Students’ Higher Order Thinking Skills - Ramirez, Rachel Patricia B.; Ganaden, Mildred S. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol. 66, No. 1 (December 2008), 2010)
This study investigated the effects of creative activities on high school chemistry students’ higher order thinking skills. Sixty (60) students were assigned randomly into Instruction with Creative Activities (ICA) group and Instruction with No Creative Activities (INCA) group. Various creative activities were incorporated into fourteen lessons of the ICA group in the intervention which lasted for ten weeks. The group exposed to the ICA was expected to have a higher mean score in the Chemistry Test for Higher Order Thinking Skills (ChemTHOTS). However, no significant difference was found between the mean posttest scores of the ICA and INCA in the ChemTHOTS. Moreover, no significant difference was found between the mean gain score from pretest to posttest of the two groups.